Accelerating the end of hunger and malnutrition: A global event: Synopsis - International Food Policy Research Institute (Food and Agriculture Organization of the United Nations, 2019)
The world faces a fast-approaching due date: 2030 is the year by which 193 countries have committed themselves to ending hunger and malnutrition as part of the Sustainable Development Goals (SDGs). This commitment is supported by the UN Decade of Action on Nutrition (2016–2025), designed to promote the achievement of SDG2—a necessary condition for most other SDGs—and the Compact2025 initiative, which was established to use data, research-based evidence, best practices, and South-South learning to accelerate progress in ending hunger and malnutrition. These efforts, however, represent only the first step along the path toward achieving a world free of hunger and malnutrition. Success depends on following up commitments with concerted actions that produce measurable and sustainable results. So far, the evidence shows that the world is moving far too slowly along this path. Despite the political will expressed in the SDGs, hunger persists, and malnutrition is climbing. These realities—and the conviction that the world could move faster—were the impetus and the backdrop for an international three-day conference—organized by the International Food Policy Research Institute (IFPRI) and the Food and Agriculture Organization of the United Nations (FAO)—in Bangkok in November 2018. At the conference, more than 600 distinguished decisionmakers, practitioners, and other stakeholders—from across governments, NGOs, civil society, research organizations, and the private sector— gathered to discuss how to speed up progress. In a wide-ranging set of keynote addresses, panel discussions, and side events, they shared evidence and lessons learned from around the world on transforming food systems to reduce hunger and malnutrition. They explored opportunities for scaling up successful actions and innovations that can disrupt business-as-usual to build momentum and accelerate progress.